Development, governmentality and the sedentary state: the productive safety net programme in Ethiopia's Somali pastoral periphery. Issue 6 (19th September 2022) - Alene, Getu Demeke; Duncan, Jessica; van Dijk, Han
ABSTRACT: This paper explores how the Productive Safety Net Programme (PSNP), as an example of contemporary bottom-up development practices in the global South, governs nomadic pastoralists in the peripheries. Based on fieldwork in Ethiopia's Somali region, we show that PSNP practices of client targeting, community-based public works and (international) financial resource flows, both for their own sake and because of their entanglement with the sedentary metaphysics of Ethiopian state, have advanced sedentary governmental order into pastoral peripheries more than top-down state sedentarization interventions had ever done. Finally, we argue that bottom-up development practice is an effective tool for state-building in the periphery.